Spiritual Intelligence Roles to Improve the Quality of Nursing Care: A Systematic Review - Kornelis Nama Beni; Nisa Dewanti; Ida Yanriatuti; Mira Melynda Prakosa; Sena Purwanza (Universitas Airlangga, 2019)
Introduction: The quality of nursing care is the most significant predictor of patient satisfaction in care. But the fact is that nurses have not shown an increase in the quality of nursing care. Lack of sense of responsibility, sincerity, self-awareness and professionalism is an indicator of the poor quality of nursing care in the health care system. The aim of the systematic review was conducted to examine the role of spiritual intelligence to improve the quality of nursing care.Method: A systematic search was conducted in Pub Med, Science Direct, Research Gate, and Emerald Insight data based. The search was identified 15 relevant original articles and full text published between 2013 until 2018.Result: The result showed that Spiritual Intelligence could be improving the quality of nursing care. Nurse with high spiritual intelligence have more competence, personal meaningful about caring, moral performance, personal excellence and flexibility were effective in increasing the quality of care.Conclusion: Spiritual intelligence has strengthened the beliefs and personality of nurses and the desire to grow and learn, work more professionally in improving the quality of nursing care. Because there was a lack in the reviewed studies used the cross-sectional and correlation, well-designed such as randomised controlled trials or queasy experiment should be conducted to more objectively evaluated the effect of spiritual intelligence to improve the quality of nursing care